Let AB = x
PB = x/4
Therefore;
a = x - (x/4)
a = (3x/4) units.
b² = x²+(3x/4)²
b = √(x²+(3x/4)²) units.
c = (x-4) units.
It implies that;
½(x*(3x/4)) + ½(4*√(x²+(3x/4)²)) + ½(4*(x-4)) + (4*4) + ½((x/4)+4)*(x-4) = x²
⅛(3x²) + 2√(x²+(3x/4)²) + 2(x-4) + 16 + ½(¼(x+16))(x-4) = x²
2√(x²+(3x/4)²) + 2x + 8 + ⅛(x²+12x-64) = ⅛(5x²)
16√(x²+(3x/4)²)+16x+64+x²+12x-64 = 5x²
16√(x²+(3x/4)²)+28x = 4x²
Dividing through by 4
4√(x²+(3x/4)²)+7x = x²
16(x²+(9x²/16)) = x⁴-14x³+49x²
16(25x²/16) = x⁴-14x³+49x²
25x² = x⁴-14x³+49x²
Dividing through by x²
25 = x²-14x+49
x²-14x+24 = 0
x²-12x-2x+24 = 0
x(x-12)-2(x-12) = 0
(x-12)(x-2) = 0
x ≠ 2
x = 12 units.
Where x is the side of the square.
We appreciate you contacting us. Our support will get back in touch with you soon!
Have a great day!
Please note that your query will be processed only if we find it relevant. Rest all requests will be ignored. If you need help with the website, please login to your dashboard and connect to support